1985
DOI: 10.1128/aem.49.5.1342-1344.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Toxicity of a Cyanobacterium ( Microcystis aeruginosa ) under Culture Conditions

Abstract: Effects of light intensity, temperature, and nutrients on the toxicity of Microcystis aeruginosa were investigated, using a toxic strain which kills mice. A marked change in toxicity was observed in the light intensity experiment, and slight changes were observed to be caused by temperature and phosphorus deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1
4

Year Published

1991
1991
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(118 citation statements)
references
References 8 publications
8
105
1
4
Order By: Relevance
“…Previous culture-based studies have shown only a onefold to twofold increase in microcystin quotas when temperatures have been increased in > 5°C increments (e.g. Watanabe and Oishi, 1985). Significant spikes in light intensity were recorded but these did not start until after 1300 h (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Previous culture-based studies have shown only a onefold to twofold increase in microcystin quotas when temperatures have been increased in > 5°C increments (e.g. Watanabe and Oishi, 1985). Significant spikes in light intensity were recorded but these did not start until after 1300 h (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Traditionally, the regulation of microcystin biosynthesis has been studied using toxin analysis. Earlier studies conducted during the 1980s employed mouse bioassays (e.g., Watanabe and Oishi 1985;van der Westhuizen and Eloff 1985) and with the advancement of analytical and biochemical methodologies at the onset of the 1990s more sophisticated techniques such as nuclear magnetic resonance spectrometry coupled with mass spectrometry (e.g., Sivonen et al 1990), high pressure liquid chromatography (e.g., Sedmak and Kosi 1998), enzyme-linked immunosorbent assays (e.g., Chu et al 1990), and protein phosphatase inhibition assay (e.g., Yoshizawa et al 1990) have been used, which have greatly improved the capability of toxin detection, quantification, and toxicity assessment. However, despite progress, the regulation of microcystin production is still poorly understood, demonstrating that toxin analysis alone is unlikely to be capable of assessing the full extent and complexity of the genetic and biosynthetic regulatory mechanism of microcystin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The global relevance of MCs and Microcystis has led to dedicated efforts toward elucidating the role of this toxin in cyanobacteria metabolism and the factors regulating its biosynthesis. A good number of studies have shown that nutrients (Rapala et al 1997;Orr and Jones 1998;V ezie et al 2002;Xu et al 2010), temperature (Watanabe and Oishi 1985; Am e and Wunderlin 2005; Davis et al 2009), light (Kaebernick et al 2000;Kardinaal et al 2007;Leblanc Renaud et al 2011), andpH (Van Der Westhuizen andEloff 1983;Kr€ uger et al 2012) affect cyanobacterial growth and microcystin production in various ways. Results from many of these studies are rather contradictory; hence the precise biological function of MCs and the factors regulating its production are still contentious.…”
Section: Introductionmentioning
confidence: 99%